The Role of Technological Culture in Enhancing Electronic Human Resource Management Practices: An Exploratory Study of the Opinions of a Sample of Human Resource Managers in Public Universities in the Kurdistan Region of Iraq - Azad Hussain Taha; Hadi Khalil Ismail (TANMIYAT AL-RAFIDAIN, 2026)
Technological culture contributes to supporting the effective implementation of electronic human resource management practices by enhancing digital skills and fostering acceptance of digital transformation within organizations. The study stemmed from a field problem that raised the following question: Does technological culture contribute to enhancing electronic human resource management practices in public universities in the Kurdistan Region–Iraq? The main objective of the study was to examine the role of technological culture in enhancing electronic human resource management practices. To achieve this objective, the descriptive–analytical approach was adopted for data collection and analysis, based on a questionnaire distributed to a sample of 194 human resource managers in the surveyed universities. The data were analyzed and the hypotheses were tested using a set of appropriate statistical methods available in the statistical software (SPSS V.27). The results indicated high levels of technological culture practices in the surveyed universities, represented by its dimensions (cognitive, skill-based, ethical, and social), as well as high levels of implementation of electronic human resource management practices. Moreover, the findings revealed a statistically significant positive effect of technological culture on electronic human resource management practices. Accordingly, several recommendations were proposed to enhance technological culture in the surveyed universities and to strengthen the implementation of electronic human resource management practices, in addition to suggesting directions for future research.